Index of Student Satisfaction with Service at the Faculty of Economics, Batanghari Jambi University - M Alhudhori; Amalia Paramita Sari (Universitas Batanghari, 2021)
This research aims to find out the academic service to students at the Faculty of Economics, Batanghari Jambi University and to find out student satisfaction with Academic service at the Faculty of Economics, Batanghari Jambi University. The variable in this research is one, namely student satisfaction with academic service. The sample in this study was all students of the Faculty of Economics unbari numbered 81 people. The instruments used in this study are documentation to obtain forms of academic service and questionnaires to obtain student satisfaction scores for academic service. Data analysis techniques used are quantitative descriptive analysis techniques using percentage formulas to answer the second problem formulation. Through the method and analysis of the data showed that the level of student satisfaction with academic service at the Faculty of Economics, Batanghari Jambi University, was a student who was in the high category was 6 people with a percentage of 7.4%, and those in the moderate category were 58 people with a percentage of 71.6%, while the lowest chose were 17 people with a percentage of 20.9%. Thus the level of student satisfaction with academic services at the Faculty of Economics, Batanghari Jambi University is in the moderate category of 58 students with a percentage of 71.6%.